2022
DOI: 10.3389/fmed.2021.812775
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Comorbidities and Airway Clearance on Mortality and Outcomes of Patients With Severe Bronchiectasis Exacerbations in Taiwan

Abstract: Bronchiectasis is characterized by systemic inflammation and multiple comorbidities. This study aimed to investigate the clinical outcomes based on the bronchiectasis etiology comorbidity index (BACI) score in patients hospitalized for severe bronchiectasis exacerbations. We included non-cystic fibrosis patients hospitalized for severe bronchiectasis exacerbations between January 2008 and December 2016 from the Chang Gung Research Database (CGRD) cohort. The main outcome was the 1-year mortality rate after sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Moreover, having P. aeruginosa isolates; concomitant NTM and P. aeruginosa isolates; and concomitant NTM, P. aeruginosa , and fungus isolates were associated with a high risk of ventilator use and mortality. Recently, Huang et al demonstrated BACI score ≥ 6 had a significantly higher cumulative incidence of respiratory failure and mortality after severe bronchiectasis exacerbations ( Huang et al, 2021 ). We also showed that high BACI score independently predicted respiratory failure and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, having P. aeruginosa isolates; concomitant NTM and P. aeruginosa isolates; and concomitant NTM, P. aeruginosa , and fungus isolates were associated with a high risk of ventilator use and mortality. Recently, Huang et al demonstrated BACI score ≥ 6 had a significantly higher cumulative incidence of respiratory failure and mortality after severe bronchiectasis exacerbations ( Huang et al, 2021 ). We also showed that high BACI score independently predicted respiratory failure and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This study retrieved demographic data; laboratory, microbiology, and pulmonary function reports; and medical records from the CGRD. The BACI score was calculated on the basis of comorbidities observed from diagnoses in the CGRD ( 2 , 3 ). This study also collected sputum microbiology reports.…”
Section: Methodsmentioning
confidence: 99%
“…Comorbidities are prevalent in patients with bronchiectasis and contribute to increased mortality ( 2 ). Bronchiectasis with comorbidities can be evaluated using bronchiectasis etiology comorbidity index (BACI) to predict clinical outcomes ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In critical patients infected with influenza, bacterial co-infection and its complications, such as development of acute respiratory distress and acute kidney injury, contribute to the mortality associated with influenza [ 11 , 12 , 13 , 14 , 15 ]. In our recent study, the common existing bacterial pathogens in acute exacerbations of bronchiectasis were Pseudomonas aeruginosa , followed by Klebsiella pneumoniae and Haemophilus influenzae [ 16 ]. Whether this underlying chronic infection leaves bronchiectasis patients particularly vulnerable to influenza infections is not known.…”
Section: Introductionmentioning
confidence: 99%